A Novel Understanding of Phocidae Hearing Adaptations Through a Study of Northern Elephant Seal (Mirounga angustirostris) Ear Anatomy and Histology. Issue 9 (3rd December 2018) - Smodlaka, Hrvoje; Khamas, Wael A.; Jungers, Hali; Pan, Roman; Al‐Tikriti, Mohammed; Borovac, Josip A.; Palmer, Lauren; Bukac, Martina
ABSTRACT: The most conspicuous aural adaptation in northern elephant seals (NES) is complete absence of an auricle and a tortuous collapsed external acoustic meatus. The NES epitympanic recess contains massive ossicles immersed in the middle ear cavernous sinuses. Engorgement of the cavernous sinuses would make ossicles fully buoyant during deep diving. NES have a comparatively larger cochlear nerve, which carries a significantly larger number of axons than in terrestrial mammals, which would give them auditory ability similar to the obligate marine mammals such as cetaceans. Our calculations show that the traditional "air‐dependent" impedance matching mechanism in NES functions to just half of the capacity compared with the one described in terrestrial mammals. Impedance matching would be further hindered in NES while diving due to fully collapsed external acoustic meatus. Thanks to similarities of acoustic impedance between the sea water, soft tissues, and blood sinuses, very little sound energy would be reflected and lost. When sound is generated underwater, the large ossicles, buoyant in the cavernous sinus, would not move due to oscillation of tympanic membrane. Rather, they would be oscillating due to their inertia and process of acoustic streaming. Our mathematical simulation shows that an increase in sound frequency would cause increased displacement of the stapedial footplate and thus transmit the sound energy to the inner ear. We contend that during diving, impedance matching and sound signal amplification in the middle ear courses through the cavernous sinuses and oscillates the enlarged ossicles, thus enabling a high‐frequency ultrasonic hearing range in Phocidae. Anat Rec, 302:1605–1614, 2019. © 2018 American Association for Anatomy